2016
DOI: 10.3390/pathogens5030047
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Factor H to the Streptococcus suis Cell Surface is Multifactorial

Abstract: Streptococcus suis is an important bacterial swine pathogen and a zoonotic agent. Recently, two surface proteins of S. suis, Fhb and Fhbp, have been described for their capacity to bind factor H—a soluble complement regulatory protein that protects host cells from complement-mediated damages. Results obtained in this study showed an important role of host factor H in the adhesion of S. suis to epithelial and endothelial cells. Both Fhb and Fhbp play, to a certain extent, a role in such increased factor H-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
0
27
1
1
Order By: Relevance
“…A Fhb knockout mutant was shown to present lower survival in the presence of human blood and neutrophils and being less virulent in a pig experimental infection model . However, in our hands and using a similar mutant, we could not demonstrate any differences in phagocytosis by human macrophages and bacterial survival in whole swine blood when compared to the wild‐type strain . On the other hand, Fhbp shares similarity with the S. pneumoniae PspC protein, also possessing a factor H‐binding activity .…”
Section: How Does Streptococcus Suis Fight Against Early Host Immune contrasting
confidence: 60%
See 1 more Smart Citation
“…A Fhb knockout mutant was shown to present lower survival in the presence of human blood and neutrophils and being less virulent in a pig experimental infection model . However, in our hands and using a similar mutant, we could not demonstrate any differences in phagocytosis by human macrophages and bacterial survival in whole swine blood when compared to the wild‐type strain . On the other hand, Fhbp shares similarity with the S. pneumoniae PspC protein, also possessing a factor H‐binding activity .…”
Section: How Does Streptococcus Suis Fight Against Early Host Immune contrasting
confidence: 60%
“…Another protein, a factor H‐binding protein (Fhb) , has an N ‐terminal domain that is identical to SadP and it specifically recognizes Galα1‐4Gal, the disaccharide truncation form of the glycolipid GbO3 . In addition, it has been very recently reported that host factor H is able to act as a bridge between bacteria and epithelial cells, increasing bacterial adhesion to respiratory cells . However, receptors involved in such interactions have not been yet identified.…”
Section: How Does Streptococcus Suis Establish In Mucosa and Breakdowmentioning
confidence: 99%
“…None of the latter possessed IgM cleaving activity. We hypothesized that upon IgM cleavage, Fc fragments would become detached from the bacterial surface, whereas F(ab’)2 fragments might remain attached to it as Ide Ssuis cleaves the heavy chain of IgM at the N-terminus of the C3 domain [9]. We therefore analyzed bacterial labeling with IgM using IgM-F(ab’)2 and IgM-Fc specific antibodies, that were tested in Western Blot analysis to recognize the respective parts of porcine IgM only (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virulence factors involved specifically in complement evasion on the other hand are scarce. Proven or potential candidates are the polysaccharide capsule [8], factor H binding proteins FhB and Fhbp [9] and lastly the IgM protease Ide Ssuis [10]. Ide Ssuis , expressed universally among S. suis serotypes, is a highly specific protease, with porcine IgM as its sole substrate [11].…”
Section: Introductionmentioning
confidence: 99%
“…A serotype 2 non-encapsulated mutant strain showing a high percentage of hydrophobicity was used as a positive control [33]. …”
Section: Methodsmentioning
confidence: 99%